Performance investigation of WOFDM for 5G wireless networks - M. F. Ghanim (International Journal of Electrical and Computer Engineering (IJECE), 2019)
Nowadays, emerging wireless networks scenarios such as the proposed systems for 5G is discussed widely with diverse requirements. Orthogonal Frequency Division Multiplexing (OFDM) is a conservative proposal which is used to build 5G WOFDM system (Wavelet OFDM system). The simulation of the system is initialized with BPSK then with QAM and 64-QAM the system is improved by increasing the number of levels of Discrete Wavelet Transform to five levels and finally compared with original system to prove that the it is convenient for 5G Wireless networks.